Experiences of children with trisomy 18 referred to pediatric palliative care services on two continents. Issue 6 (1st April 2019) - Mullin, Jonathan; Wolfe, Joanne; Bluebond‐Langner, Myra; Craig, Finella
Abstract: Children with trisomy 18 that survive beyond the neonatal period have multiple congenital anomalies, neurodevelopmental disability, and high mortality rates. The experience of children with trisomy 18 who receive pediatric palliative care services is largely unknown. We conducted a retrospective review of children with trisomy 18 receiving pediatric palliative care services at both Boston Children's Hospital, USA and Great Ormond Street Hospital, UK from January 1, 2004 to January 1, 2015. Fifty‐eight children with trisomy 18 were referred to pediatric palliative care, 38 in the United Kingdom, 20 in the United States. Median age at referral was 19 days (2–89) in the United Kingdom, and 25 days (1–463) in the United States. Median length of time being followed by pediatric palliative care was 32 days (1–1, 637) in the United Kingdom and 67 days (3–2, 442) in the United States. The only significant difference in the two cohorts ( p = .001) was in likelihood of receiving cardiac surgical intervention—37% in the United States, 0% the United Kingdom. Children with trisomy 18 receive pediatric palliative care services, with variable age at referral and for a variable length of time. Further research is needed to understand the experience of children with trisomy 18 and their families receiving pediatric palliative care services.